The dead shall not rest ebook - Harris, Tessa (Dr. Thomas Silkstone Mystery, 2012)
An American anatomist contends with body snatchers plaguing 1782 London in this historical mystery for fans of Caleb Carr. It is not just the living who are prey to London's criminals and cutpurses. Corpses, too, are fair game—dug up from fresh graves and sold to unscrupulous men of science. Dr. Thomas Silkstone abhors such methods, but his leading rival, Dr. John Hunter, has learned of the imminent death of eight-foot-tall Charles Byrne, known as the "Irish Giant," and will go to any lengths to obtain the body for his research. Thomas intends to see that Byrne is allowed to rest in peace. Yet his efforts are complicated by concern for his betrothed, Lady Lydia Farrell, who breaks off their engagement without explanation. When Dr. Hunter is implicated in the horrific murder of a young castrato, Thomas must determine how far the increasingly erratic surgeon will go in the name of knowledge. For as Thomas knows too well, the blackest hearts sometimes go undetected—and even an unblemished façade can hide terrifying secrets... Praise for The Dead Shall Not Rest "Outstanding.... Well-rounded characters, cleverly concealed evidence, and an assured prose style point to a long run for this historical series."— Publishers Weekly , starred review "Populated with real historical characters and admirably researched, Harris's novel features a complex and engrossing plot. A touch of romance makes this sophomore outing even more enticing. Savvy readers will also recall Hilary Mantel's The Giant, O'Brien ."— Library Journal